2013
DOI: 10.1111/jth.12331
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Ribonucleic Acid 494 regulation of protein S expression

Abstract: Summary. Background: Acquired protein S (PS) deficiency is highly associated with elevated circulating estrogen levels resulting from pregnancy, oral contraceptives, and estrogen replacement therapy; however, the mechanism of estrogen-mediated acquired PS deficiency remains poorly understood. Increasing evidence indicates that estrogen receptor signaling can indirectly modulate the expression of target genes at the post-transcriptional level by modulating the expression of microRNAs (miRNAs), and miRNAs have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…miRNA expression has been detected in anucleate platelets [24,25], exosomes [26], and microparticles [27] possessing procoagulant properties. Moreover, recent reports have demonstrated that miRNAs directly regulate hemostatic proteins, such as protein S, antithrombin, tissue factor, fibrinogen, PAI-1, and FXI [21,[28][29][30][31][32]. Collectively, these studies suggest that miRNAs play a role in haemostasis and could contribute to the pathogenesis of thrombotic disorders.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…miRNA expression has been detected in anucleate platelets [24,25], exosomes [26], and microparticles [27] possessing procoagulant properties. Moreover, recent reports have demonstrated that miRNAs directly regulate hemostatic proteins, such as protein S, antithrombin, tissue factor, fibrinogen, PAI-1, and FXI [21,[28][29][30][31][32]. Collectively, these studies suggest that miRNAs play a role in haemostasis and could contribute to the pathogenesis of thrombotic disorders.…”
Section: Discussionmentioning
confidence: 86%
“…In our study, 1-10 nmol L -1 EE2 was found sufficient to induce miR-27a and miR-27b expression levels in MCF7 cells, an effect that was evidently exerted through ERa as blocking the receptor with the ERa antagonist fulvestrant, or indeed transiently knock down of the receptor by siRNA, led to loss of the EE2-mediated induction of miR-27a/b and miR-494. In a recent study by Tay et al [28], miR-494 was reported to be induced by 1-10 nmol Fig. 6.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We demonstrated in HuH-7 liver carcinoma cells that oestrogen treatment resulted in the induction of miR-494 expression in association with downregulated levels of the anticoagulant, Protein S, indicating a mechanism for miRNA-mediated regulation of acquired Protein S deficiency, with a potential role for increased miR-494 levels in pregnant women as an indicator for high thrombotic risk [17]. It is likely that increased circulating oestrogen levels during pregnancy alters the expression of a suite of miRNAs in oestrogen-sensitive tissues, with changes in specific miRNAs possibly detectable in circulating plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Coagulation factors like fibrinogen [22] or tissue factor have been described as interacting with miRNAs, which may have an impact on the thrombotic etiology associated with pathologies such as antiphospholipid syndrome or systemic lupus erythematosus [23]. Recently, PAI-1 [24] and protein S [25] have also been shown to be directly regulated by miRNAs. In the current study, we investigated the potential relevance of miRNAs aiming to discover new elements that may modulate FXI in the liver.…”
Section: Introductionmentioning
confidence: 99%